Aspek Gramatikal dan Leksikal Pada Lirik Lagu â€œAku Cinta Allahâ€ Group Band Wali - Sari, Intan Purnama; Setyorini, Ririn (Universitas Hamzanwadi, 2018)
This research is to describe (1) how is the form of grammatical cohesion in the song lyrics of